THE INFLUENCE OF FUNCTION, FORM AND STRUCTURE ON THE SPATIAL HIERARCHY OF THE TAWANG RAILWAY STATION IN SEMARANG - Beni Adi Santoso, Bachtiar Fauzy (Riset Arsitektur (RISA), 2017)
Abstract - Dutch East Indies Empire architecture in Indonesia must be preserved as a result of acculturation between a foreign culture and a local one. The century-old Tawang Railway Station in Semarang has been hit by annual rob floods and has undergone somerenovation, but the latter has made the impact of reducing the architectural values of “Indies” style in its features. This research study may deepen understanding of this type of colonial architecture, exploring its application to this railway station. Furthermore, an in-depth analysis determines how function, form and structure have affected the spatial hierarchy of this railway station. This study is descriptive, analytical and interpretative, employing theories dealing with archetypes, ordering principles and Dutch East Indies Empire architecture. After data collection, the analysis compares these theories with the object of study. The findings indicate that this station has indeed applied the concept of the Dutch colonial style, starting from the context of the local area to the building elements, except for the floor. At present, the latter has already been changed in its entirety, from the initial building stage to its current state, where the specific “Indies” character can no longer be discerned. The zenith of hierarchy can be observed in the main lobby whose function is to receive visitors in its cube-shaped space similar to the Sokoguru (central Javanese pillar) and the cupola not found in any other part of the building. The building mass of the station is symmetrical in keeping with its typical “Indies” character, but the function of the interior space is asymmetrical. This shows the importance of achieving a high degree of spatial efficiency to make the activities run smoothly and effectively. Keywords: Hierarchy, Space, Dutch East Indies Empire Architecture, Semarang’s Tawang Railway Station